Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak UMKM dengan Sosialisasi Perpajakan sebagai Variabel Moderasi - Susan, Susan; Melzatia, Shinta (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of taxation knowledge, taxpayer awareness, and tax sanctions on MSME taxpayer compliance with tax socialization as a moderating variable. This study uses the slovin formula for sampling by distributing questionnaires. The data used is primary data sourced from distributing questionnaires to 100 MSME taxpayers in DKI Jakarta. The data analysis method is Moderated Regression Analysis (MRA) which is used to understand whether the effect of the independent variable on the dependent variable is influenced by the moderating variable. This research is a type of causal research that aims to determine the cause - effect between variables. This study uses a quantitative research design to collect a number of data that is useful for explaining the characteristics of each variable with other variables. The results of this study indicate that taxpayer awareness has a positive effect on MSME taxpayer compliance, while the tax knowledge variable, and tax sanctions have no effect on MSME taxpayer compliance. Tax socialization cannot moderate tax knowledge, taxpayer awareness, and tax sanctions on the compliance of MSME taxpayers in DKI Jakarta. Keywords: Taxpayer Awareness, Taxpayer Compliance, Taxation Knowledge, Tax Sanctions, Taxation Socialization.